2009
DOI: 10.1111/j.1610-0387.2008.06941.x
|View full text |Cite
|
Sign up to set email alerts
|

Telangiectasia macularis eruptiva perstans, a form of cutaneous mastocytosis, associated with malignant melanoma

Abstract: A 62-year-old obese woman presented with a malignant melanoma (Stage la). In addition, she had disseminated telangiectatic macules on both thighs. Intensive rubbing of lesions resulted in wheals. Biopsy revealed increased numbers of mast cells. We diagnosed telangiectasia macularis eruptiva perstans, a rare clinical form of adult maculopapular cutaneous mastocytosis, a group which also includes urticaria pigmentosa. No evidence was found for systemic involvement. Possible associations with malignant tumors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
(19 reference statements)
0
15
0
Order By: Relevance
“…In the fourth case, malignant melanoma was diagnosed prior to SM (7). And finally, a patient with telangiectasia macularis eruptive perstans (TEMP), a rare form of cutaneous mastocytosis, was found to have a malignant melanoma (8).…”
mentioning
confidence: 99%
“…In the fourth case, malignant melanoma was diagnosed prior to SM (7). And finally, a patient with telangiectasia macularis eruptive perstans (TEMP), a rare form of cutaneous mastocytosis, was found to have a malignant melanoma (8).…”
mentioning
confidence: 99%
“…6 A variety of non-hematological neoplasms have been reported in patients with mastocytosis, although rarely in the same histological sample. 5 To our knowledge, only 3 cases of mastocytosis associated with benign melanocytic nevi and 2 cases of mastocytosis associated with melanoma are reported in the literature, [1][2][3][4][5] but never in the same patient. In our case, consistently with the clinical and histological findings, the presence of a double cellular proliferation could have a physiopathological linkage, rather than be ascribed to a mere coincidence.…”
Section: Discussionmentioning
confidence: 97%
“…[1][2][3][4][5] Some authors reported cutaneous mastocytosis complicating pregnancy and recently Zaitsu et al found that binding estradiol to estrogen receptor-α on the membrane of mast cells supports the synthesis and release of mast cell mediators in vitro. 13,14 However, although currently there are no reliable data of a possible carcinogen role of the estrogens on the development of melanoma and/or on the exacerbation of the mastocytosis, it may be hypothesized that this is an additional linkage between the diseases, even though not yet so well explored.…”
Section: Figure 4 (A) Superficial Spreading Melanoma With Underlying mentioning
confidence: 99%
See 1 more Smart Citation
“…Two case reports of association between MM and cutaneous mastocytosis occurred in adult females have been described in the literature, both suggesting oestrogens as a possible pathogenic link. This is the third such case, and is the first in a male patient.…”
mentioning
confidence: 99%